Orrella amnicola sp. nov., isolated from a freshwater river, reclassification of Algicoccus marinus as Orrella marina comb. nov., and emended description of the genus Orrella. Issue 12 (28th December 2020) - Sheu, Shih-Yi; Chen, Li-Chu; Yang, Che-Chia; Carlier, Aurelien; Chen, Wen-Ming
Abstract : A novel Gram-negative, aerobic, non-motile, ovoid to rod-shaped bacterium, designated NBD-18 T, was isolated from a freshwater river in Taiwan. Optimal growth occurred at 30 °C, at pH 6 and in the absence of NaCl. The predominant fatty acids of strain NBD-18 T were C16 : 0, summed feature 3 (C16 : 1 ω 7 c and/or C16 : 1 ω 6 c ), C17 : 0 cyclo and summed feature 8 (C18 : 1 ω 7 c and/or C18 : 1 ω 6 c ). The major polar lipids were phosphatidylethanolamine, phosphatidylglycerol, diphosphatidylglycerol and phosphatidyldimethylethanolamine. The major polyamine was putrescine. The major isoprenoid quinone was Q-8. The genomic DNA G+C content of strain NBD-18 T was 50.9 %. Strain NBD-18 T was most closely related to Orrella dioscoreae LMG 29303 T and Algicoccus marinus HZ20 T at a 16S rRNA gene sequence similarity of 97.7 %. 16S rRNA gene sequence similarity between O. dioscoreae LMG 29303 T and A. marinus HZ20 T was 97.7 %. Phylogenetic analyses based on 16S rRNA gene sequences and an up-to-date bacterial core gene set indicated that strain NBD-18 T, O. dioscoreae LMG 29303 T and A. marinus HZ20 T are affiliated with the same genus. Digital DNA–DNA hybridization, average nucleotide identity and average amino acid identity values among these three strains supported that they belong to the same genus and that strain NBD-18 T represents a novel species. Thus, A. marinus HZ20 T should be reclassified as Orrella marina comb. nov. based on the rules for priority of publication and validation. On the basis of the genotypic, chemotaxonomic and phenotypic data, strain NBD-18 T represents a novel species in the genus Orrella, for which the name Orrella amnicola sp. nov. is proposed. The type strain is NBD-18 T (=BCRC 81197 T =LMG 31338 T ).